DESIGN AND IMPLEMENTATION OF 240L SQUARE BIN CAPACITY MEASUREMENT USING 5 ULTRASONIC SENSOR CONFIGURATION - Al Faruqi, Muhammad
Waste management has a long process. The problem often arises in waste management is the bins have uncertain time to full. The stakeholder doesn’t have enough data to make decision to overcome this problem. A system is needed to provide bin’s capacity data over time as a basis for making decision. Bin’s capacity measurement is commonly done by measuring the height of trash heap using distance sensor. Garbage have random positions and various contour. Thus, measuring bin’s capacity using just one sensor is not enough to get data that describe the contour. By spreading 5 sensors on the bin’s lid to form letter “X” position, garbage level data at 5 different points is obtained. This 5 data is used as a basis to calculate bin’s capacity level. Measurement using 5 sensors represents the garbage’s contour.